Oral health literacy in Malang City, Indonesia - Rara Warih Gayatri; Ema Novita Deniati; Roslan bin Saub (AOSIS, 2022)
Dental and oral health are the main indicators of health, well-being, and quality of life. The concept of Oral Health Literacy (OHL) has become important because it regards individual capacity to understand and use dental information to transform into oral health behaviours. Thus, the aim of this study was to discover and describe the OHL status of adults in Malang City and its relationship with sociodemographic status so that it can be used as a basis for making policy. This study used observational analytical study design involving 450 respondents in Malang by quota random sampling method. The data was collected by the self-administered 29-item HeLD-ID (Health Literacy in Dentistry Indonesian Version) questionnaire. The study resulted that the overall HeLD-ID score was 3.68±0.69. The HeLDID score significant difference was affected by sex (p<0.05) and the other sociodemographic determinants (age, last education, and income) were not. However, there were significant differences of HeLD scores in communication domain (p<0.05) affected by age, sex, and income.